Pendampingan Relawan Matematika Asyik (Rematika) Terhadap Siswa di Sekolah dan Anak-Anak Nelayan Pinggir Pantai Kenjeran Surabaya - Hidayatullah, Achmad (Universitas Muhammadiyah Surabaya, 2018)
So far, mathematics has become a difficult subject for students. Therefore some parents choose the way to bring in private teachers to help their children understand math. This devotion is the accompaniment of learning for students at SD Muhammadiyah 18 Surabaya and the fisherman children who are still in school kenjeran surabaya area. This devotion is done by a number of fun mathematical realists (REMATIKA) Muhammadiyah University of Surabaya. The volunteers make the media of learning innovation a number of seven media to help students memmami math with fun and fun way. Among them are learning of the set with the media of smart dolls (BOPIN), smart turtle, KOTAMAT (mathematical box), FRAMEWORK (mathematical war tower), Kurung Sakti, and Pirates of Mathematics